Formation of failure relief in the conditions of mining landscapes of the Kryvyi Rih landscape-technical system - Koptieva, T. S. (Man and Environment. Issues of Neoecology, 2025)
Purpose. To establish the patterns of formation and development of the failed relief as a transitional tier of the two-tier structure of mining landscapes of the Kryvyi Rih landscape-technical system and to assess its impact on the modern morphodynamics of the Kryvyi Rih landscape-technical system.Methods. Field observations, geomorphological analysis, comparative-analytical method, cartographic modelling, GIS analysis.Results: The relief is one of the key morphological elements of the two-tier structure of the mining landscapes of the Kryvyi Rih landscape-technical system. It was determined that the most intense zones of displacement are recorded within the boundaries of Sukha Balka OJSC, the Kolachevsky and Galkovsky ore management departments, the Oleksandrivsky mine, and the Kozatska mine. Two groups of sinkhole processes have been recorded: regular ones associated with planned mining activities and random ones caused by uncontrolled geodynamic factors. It has also been found that sinkholes form not only above mine workings, but also within the dumps located above them. The largest subsidence forms, in particular the subsidence zone of the Kozatska mine and the Galkovsky corner zone, demonstrate the high intensity of modern deformations of the earth's surface. Geomorphological analysis revealed the structural and morphological features of the two-tier structure of mining landscapes and traced the relationship between surface and underground processes. The comparative-analytical method made it possible to compare the current state of subsidence formations with data from previous observations, revealing a tendency towards an increase in the area of deformation zones. Cartographic modelling enabled the construction of maps showing the spatial distribution of subsidence zones within the main ore mining areas, while GIS analysis enabled the visualisation of spatial connections between surface and underground layers.Conclusions: The collapsed relief is an integral component of the two-tier structure of the mining landscapes of the Kryvyi Rih landscape-technical system. It is formed as a transitional tier that connects the surface and underground levels, providing a morphogenetic link between them. Collapse processes are regular and random in nature, indicating the complex geodynamic activity of technogenically transformed massifs. The results obtained confirm the need for further monitoring of technogenic processes to prevent the development of dangerous situations and stabilise the landscape structure of the region.